Interactive Learning Multimedia Containing Balinese Traditional Games in Thematic Learning - Putu Sandhita Prayoga; Desak Putu Parmiti; I Gede Margunayasa (Indonesian Journal Of Educational Research and Review, 2022)
The lack of availability of interactive learning multimedia based on Android applications containing local wisdom that can be used in learning causes the use of technology-based learning media to be less than optimal. This study aims to produce Interactive Learning Multimedia Containing Local Wisdom Balinese Traditional Games in Thematic Learning for Grade V Elementary School. This study uses the ADDIE development model. The research subjects are lecturers who are experts in learning media and content experts for elementary thematic learning, practitioners (teachers), and fifth-grade elementary school students. The research instruments were in the form of questionnaires and tests. Data analysis used quantitative descriptive analysis and inferential statistics. The research results are Interactive Learning Multimedia Loaded with Local Wisdom of Balinese Traditional Games in the Thematic Learning for Grade V Elementary School, with a validity of 95.79% from learning media experts and 93.85% from elementary thematic learning content experts. The level of practicality is 97.33% of practitioners and 98.33% of students. The effectiveness test results with the correlated sample t-test showed an average pre-test score of 11.52 and an average post-test score of 15.89. It was concluded that the Interactive Learning Multimedia with Local Wisdom in Traditional Balinese Games effectively improved students' thematic learning outcomes. Interactive learning multimedia makes learning more interesting and has an impact on better student learning outcomes.